Clinical implications of prolonged hyperglycaemia before basal insulin initiation in type 2 diabetes patients: An electronic medical record database analysis. Issue 3 (28th March 2019) - Raccah, Denis; Guerci, Bruno; Ajmera, Mayank; Davis, Keith; Meyers, Juliana; Lew, Elisheva; Shaunik, Alka; Blonde, Lawrence
Summary: Aims: To assess the effect of duration of hyperglycaemia before basal insulin (BI) initiation on clinical outcomes in type 2 diabetes (T2D). Materials and methods: Patients with T2D who initiated BI during 2009‐2013, had continuous enrolment for ≥2 years preceding and ≥1 year following BI initiation ("index date"), and had ≥1 glycated haemoglobin (A1C) measure not at target (ie, ≥7.0%) within 6 months preindex date were included in the study. Patients were stratified by preindex‐date duration of A1C ≥7.0%. Longitudinal A1C, weight, BMI, and diabetes medication were compared between cohorts for up to 15‐month follow‐up. Results: Of 37 053 patients who initiated BI, 40.7%, 15.3%, 16.0%, and 28.0%, respectively, had uncontrolled A1C for <6, 6‐<12, 12‐<18 and 18‐24 months preindex date. Baseline characteristics were similar between cohorts. Baseline A1C values were similar across cohorts (9.2%‐9.6%). Mean follow‐up A1C values were higher with longer preindex‐date duration of uncontrolled A1C (8.0 ± 1.7%, 8.2 ± 1.6%, 8.5 ± 1.7%, and 8.6 ± 1.7% for <6, 6‐<12, 12‐<18, and 18‐24 months); attainment of A1C <7.0% worsened with increasing preindex‐date duration of A1C ≥7.0% (29.6%, 20.0%, 14.6%, and 11.5% for <6, 6‐<12, 12‐<18, and 18‐24 months). Conclusions: These data suggest that longer duration of uncontrolled A1C before BI initiation increases the risk of not reaching glycaemic targets. However, target attainment was poor in all cohorts, highlighting inadequate glycaemic control as an important unmet need in US patients with T2D. Abstract : Real‐world data to illustrate the effect of duration of hyperglycaemia and the extent of clinical inertia, including the effects of glycaemic control, in patients with T2D would be useful. Our retrospective, real‐world data analyses suggest that delaying treatment intensification increases the risk of not meeting glycaemic targets. Such patients would benefit from initiating treatments that can improve glycaemic control without a high risk of hypoglycaemia or weight gain.